A Molecular‐Level Interface Design Enabled High‐Strength and High‐Toughness Carbon Nanotube Buckypaper. Issue 10 (25th June 2021) - Shen, Lulu; Zhao, Yushun; Owuor, Peter Samora; Wang, Chao; Sui, Chao; Jia, Shuai; Liang, Jia; Liu, Ling; Lou, Jun
Abstract: Buckypaper (BP) assembled by carbon nanotubes (CNTs) is considered as a promising macroscopic material with excellent multifunctional properties. However, the poor interfacial stress‐transfer ability between CNTs seriously limits its further applications. This paper proposes a novel approach to simultaneously improve both the tensile strength and the toughness of BPs, where a commercial poly(amido amine) (PAMAM) dendrimer is utilized to serve as an interfacial bridging agent, by realizing effective chemical cross‐linking between CNTs. The result shows that the introduction of PAMAM can increase the tensile strength, Young's modulus, and toughness by 306%, 168%, 1007%, respectively, compared with that of pristine BPs based on weak van der Waals interactions. In addition, molecular dynamics (MD) simulation is employed to reveal the proposed interfacial enhancement. It is found that the elastic deformation, uncoiling, interlocking of PAMAM dendrimers, and chemical bonds between PAMAM dendrimers and CNTs contribute to the improvement of the macroscopic strength and toughness of BPs. More importantly, it is found that the formed amido bonds are very strong, and the breakage of chemical bonds occurs at C─N bonds within PAMAM themselves. This work provides a new route for interfacial structure design and an in‐depth understanding of mechanical properties of BPs. Abstract : A novel approach is proposed to simultaneously improve both the tensile strength and the toughness of Buckypaper, where a commercial poly(amido amine) (PAMAM) dendrimer is utilized to serve as an interfacial bridging agent. Through molecular dynamics simulations, it is found that the elastic deformation, uncoiling, interlocking of PAMAM, and chemical bonds between PAMAM and carbon nanotubes contribute to the improvements.